Journey with a 21 weeks primi with acute massive pulmonary thromboembolism secondary to possible “Latent Lupus”: an audacious ride - Gomes, Richmond R (Clinical Journal of Obstetrics and Gynecology, 2022)
In pregnancy, the incidence of pulmonary embolism (PE) is increased fivefold when compared to nonpregnant women of the same age, and PE is one of the leading causes of death during pregnancy. However, the diagnosis of PE among pregnant women is complicated by concerns regarding radiation exposure. Systemic lupus erythematosus (SLE) is an autoimmune disorder with a wide array of presentations and a predilection to affect women of certain ethnic backgrounds. The hallmark of the disease is multisystem involvement, dispersed in time and severity. Usual pulmonary involvement includes pleuritis, pleural effusions, pneumonitis, shrinking lung syndrome, pulmonary hypertension, and alveolar hemorrhage. Pulmonary embolism (PE) is a relatively unusual presentation of SLE. We report the case of a 20-year-old primi at 21 weeks gestation with an acute PE with central chest pain and shortness of breath. The absence of overt signs and symptoms and traditional risk factors prompted a fragmentary workup. This led to the detection of antibodies sensitive for SLE, in the absence of overt signs and symptoms. We revive the concept of latent lupus, a condition construed as early lupus. We firmly suspect direct causation between SLE and PE. Further studies are needed to establish pathogenesis to facilitate early diagnosis and prevent morbidity and mortality from PE. Due to persistent hypotension, thrombolytic therapy with streptokinase was administered and the clinical and hemodynamic response was excellent, with no maternal or fetal hemorrhagic complications. The clinical presentation of pulmonary embolism is sometimes camouflaged by the physiological changes that occur in pregnancy and diagnosis is often delayed by a reluctance to expose the fetus to ionizing radiation.